Draft Annual Plan 1987-88 Volume-I Statement of Figures Tamil Nadu - Planning Commission (Planning Commission, 1987)
The year 1987-88 marks the reaching of mid way point in the Seventh Five Year-Plan. the Annual Plan has been formulated on the lines set out in the VII Plan, though the need for an appraisal on the allocations for certain sectors has arisen. the triple objectives of “food, work and productivity” continue to be the guiding principles for the inclusion of new activities.
State Planning Commission Tamil Nadu